Dada East? : Romanian contexts of Dadaism. - Machnicka, Zofia; Notz, Adrian; Musée des Beaux-Arts, Tourcoing (Tourcoing : Musée des Beaux-Arts., 2009)
Botea, Irina ; Cantor, Mircea ; Constantinescu, Stefan ; Farocki, Harun ; Grigorescu, Ion ; Moldovan, Sebastian ; Muresan, Ciprian ; Perjovschi, Dan ; Perjovschi, Lia ; Pogacean, Cristi et al.
Dada East? : Romanian contexts of Dadaism, Musée des Beaux-Arts, Tourcoing, 12 mars - 12 juillet 2009
boek